Characteristics of Preservice Special Education Teachers and Education Policy in Thailand - ทินมาลา ดุสิดา (Ratchaphruek Journal, 2018)
ABSTRACT This article was aimed to conceptualize special education in Thailand and analyze trends of characteristics of preservice special education teachers as followed to the changes in education policies. According to current educational policies, special education has been expansively providing to develop learners with special needs from either birth or first diagnosis throughout their lives. The ultimate goal of the education provision is to enhance people with special needs to live, learn, and work independently as dignified members in the society. Therefore, all teachers must contain academic characteristics of both special education aspects and core subjects in basic education curriculum regarding the students’ special educational needs. In terms of academic characteristics, teachers must be able to work cooperatively with stakeholders and have problem solving skills with data driven decision in order to provide educational supports effectively. The analytical article may benefit to curriculum developing teams and related educators to define desired characteristics of teachers in the future are expected.